Pre- and postharvest technologies to extend the shelf life of Prunus cerasus - Mihály, Kata; Kovács, Csilla; Takács, Ferenc; Sándor, Erzsébet (Acta Agraria Debreceniensis, 2019)
Fresh tart cherry consumption cannot be increased without the development of an appropriate technology for its elongated storage. This requires the development and optimization of the pre- and postharvest treatments. Currently, we have only limited knowledge about tart cherry (Prunus cerasus L.) postharvest technology, however, related studies on sweet cherry (Prunus avium L.) may be adopted. In this article, we have collected the most important research results in this topic.